2009
DOI: 10.1371/journal.pone.0006222
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the One-Bead One-Compound Methodology for the Design of Prolyl Oligopeptidase Substrates

Abstract: Here we describe the design, synthesis and evaluation of the first solid-phase substrates for prolyl oligopeptidase (POP), a cytosolic serine peptidase associated with schizophrenia, bipolar affective disorder and related neuropsychiatric disorders. This study seeks to contribute to the future design of a one-bead one-compound (OBOC) peptide library of POP substrates, based on an intramolecular energy transfer substrate. Unexpectedly, the enzymatic evaluation of the substrates attached on solid-phase by means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…This is a problem when screening against green fluorescentlabeled proteins. 8,18 Although Lavoie et al 19 reported intrinsic fluorescence in its screening conditions (Alexa Fluor 488 dye to label Chinese hamster ovary host cell proteins and Alexa Fluor 546 dye to label human IgG and incubated with a peptidyl ChemMatrix library), we found that this resin showed a very small autofluorescence, under the present working conditions (Figure S1B), as was reported by Comellas et al 20 Also, beads must be hydrated with buffer to avoid drying when inspected under a fluorescence microscope. Dry beads are fluorescent, and positive beads cannot be distinguished from negative beads.…”
Section: Resultssupporting
confidence: 78%
“…This is a problem when screening against green fluorescentlabeled proteins. 8,18 Although Lavoie et al 19 reported intrinsic fluorescence in its screening conditions (Alexa Fluor 488 dye to label Chinese hamster ovary host cell proteins and Alexa Fluor 546 dye to label human IgG and incubated with a peptidyl ChemMatrix library), we found that this resin showed a very small autofluorescence, under the present working conditions (Figure S1B), as was reported by Comellas et al 20 Also, beads must be hydrated with buffer to avoid drying when inspected under a fluorescence microscope. Dry beads are fluorescent, and positive beads cannot be distinguished from negative beads.…”
Section: Resultssupporting
confidence: 78%
“…Recent studies have combined a number of experimental and simulation techniques to address the details of inhibition mechanisms 17 as well as binding and gating mechanisms, 18 and progress has been made in developing combinatorial libraries for POP. 19 In this paper, our focus is on the active site access (exit) pathways. This is a fundamental question in understanding the peptidase function.…”
Section: Introductionmentioning
confidence: 99%
“…Several fundamental questions regarding access to the active site, gating, selection, and the detailed inhibition mechanisms remain unanswered. Recent studies have combined a number of experimental and simulation techniques to address the details of inhibition mechanisms as well as binding and gating mechanisms, and progress has been made in developing combinatorial libraries for POP …”
Section: Introductionmentioning
confidence: 99%
“…For example, Comellas et al (2009) reported the evaluation of solid-state peptide libraries for a cytosolic serine peptidase called prolyloligopeptidase, which is associated with schizophrenia. The objective was to learn more about the action of these enzymes and possibly discover substrates allowing a direct control.…”
Section: Present Trends and Future Prospects Of Combinatorial Peptidementioning
confidence: 99%